2012
DOI: 10.1371/journal.pone.0047264
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Vitamin D Insufficiency in China: Relationship with the Levels of Parathyroid Hormone and Markers of Bone Turnover

Abstract: There is a lack of large-scale studies on vitamin D status and its relationship to parathyroid hormone (PTH) and bone turnover markers in adults living in Shanghai. The objectives were to determine the prevalence of vitamin D insufficiency in Shanghai and to investigate the relationship of 25(OH)D with parathyroid function and bone turnover markers. This cross-sectional study involved 649 men and 1939 women aged 20–89 years who were randomly sampled in Shanghai. Serum concentrations of 25(OH)D, PTH, albumin, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
64
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(75 citation statements)
references
References 42 publications
9
64
1
1
Order By: Relevance
“…In a study from USA, the African-Americans were found to have significantly high prevalence of VDD 9 . In china too, during the winter season, the prevalence of vitamin D insufficiency (<30 ng/mL) was 84% in males and 89% in females 10 . However, in India, studies conducted even in summer showed significant VDD.…”
Section: Discussionmentioning
confidence: 95%
“…In a study from USA, the African-Americans were found to have significantly high prevalence of VDD 9 . In china too, during the winter season, the prevalence of vitamin D insufficiency (<30 ng/mL) was 84% in males and 89% in females 10 . However, in India, studies conducted even in summer showed significant VDD.…”
Section: Discussionmentioning
confidence: 95%
“…Given that absence of seasonal variation of 25(OH) D levels in our cohort, our findings seem to emphasize the influence of confounding variables, such as weight status, calcium intake and calcium absorption on elevation in PTH levels [17] [27] [36] [43].…”
Section: Discussionmentioning
confidence: 90%
“…In this regard, two points must be taken into consideration. Firstly, in all these, and many other studies, the cutoff used for serum 25(OH)D to define vitamin D inadequacy is 75 nmol/L (16)(17)19) or even higher (18). In the current study, we categorized calcidiol concentrations less than 50 nmol/L as poor vitamin D status, according to the Institute of Medicine (IOM) (20).…”
Section: Discussionmentioning
confidence: 97%